Evaluation of rice (Oryza sativa) hybrids in terms of growth and physiological parameters and their relationship with yield under transplanted condition* - SWAIN, P; P00NAM, ANNIE; RAO, K S (The Indian Journal of Agricultural Sciences, 2011)
Among the 7 rice (Oryza sativa L.) hybrids (both released and pre released) with 3 local checks tested under field condition, ’PA 6201’ was found to be most efficient with maximum leaf area index and total chlorophyll content at all be growth stages, least tiller mortality (7.6%) at maximum tillering stage, highest grain yield (6.4 tonnes/ha), grain Number/n12 (35 379) and harvest index (0.48) with moderate sterility (26%) and panicle number/m2 (336) at maturity. Check variety ’IR 64’ with high translocation efficiency, 1000-grain weight and lowest spikelet sterility recorded grain yield of 5.6 tonnesiha that was at par with ’PA 6201 ’. Grain yield was significantly correlated with leaf area index and total dly matter at post flowering stage, panicle number/m2, grain numberirn’ and harvest index at maturity. High significant positive relation of total chlorophyll content at all the growth stages with grain number/m2 indicated the role of chlorophyll content towards governing sink development and grain filling leading to higher productivity in ’PA 6201’.